From Polluting to Green Jobs : A Seamless Transition in the U.S.? - Bergant, Katharina; Mano, Rui.; Shibata, Ippei.. (Washington, D.C. : International Monetary Fund, 2022)
What are the implications of the needed climate transition for the potential reallocation of the U.S. labor force? This paper dissects green and polluting jobs in the United States across local labor markets, industries and at the household-level. We find that geography alone is not a major impediment, but green jobs tend to be systematically different than those that are either neutral or in carbon-emitting industries. Transitioning out of pollution-intensive jobs into green jobs may thus pose some challenges. However, there is a wage premium for green-intensive jobs which should encourage such transitions. To gain further insights into the impending green transition, this paper also studies the impact of the Clean Air Act. We find that the imposition of the Act caused workers to shift from pollution-intensive to greener industries, but overall employment was not affected.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Demographic Trends, Macroeconomic Effects, and Forecasts; Environmental Economics; Green and Polluting Employment; Job, Occupational, and Intergenerational Mobility; Promotion